Dnase1‐deficient mice spontaneously develop a systemic lupus erythematosus‐like disease. Issue 4 (21st February 2019) - Kenny, Elaine F.; Raupach, Bärbel; Abu Abed, Ulrike; Brinkmann, Volker; Zychlinsky, Arturo
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that has high morbidity and can result in multi‐organ damage. SLE is characterized by dysregulated activation of T‐ and B‐lymphocytes and the production of autoantibodies directed against nuclear components. The endonuclease deoxyribonuclease 1 (DNase1) is abundant in blood and a subset of SLE patients have mutations in DNASE1 . Furthermore, a report showed that Dnase1 ‐deficient mice develop an SLE‐like disease, but these mice also carry a deletion of the gene adjacent to Dnase1, which encodes the chaperone TRAP1/HSP75. We generated a murine strain deficient in Dnase1 with an intact Trap1 gene to examine if a lack of DNase1 is responsible for the development of a spontaneous SLE‐like disease. We show that the Dnase1 ‐deficient mice do indeed develop an SLE‐like phenotype with elevated autoantibody production by 9 months and kidney damage by 12 months. Notably, this model recapitulates the female bias seen in human SLE patients since female Dnase1 ‐deficient mice produced the highest concentrations of autoantibodies and had more severe kidney damage than males. Since there is currently no cure for SLE the protective role of DNase1 as demonstrated in our study remains of great therapeutic interest. Abstract : In healthy individuals, DNAse1 cleaves extracellular DNA. When this enzyme is absent, the excess DNA induces autoantibodies that lead to tissue damage (nephritis). Dnase1 deficiency in a murine model leads to a Systemic Lupus Erythematosus‐like disease.